2013
DOI: 10.1063/1.4773319
|View full text |Cite
|
Sign up to set email alerts
|

Non-Markovian stochastic Schrödinger equation at finite temperatures for charge carrier dynamics in organic crystals

Abstract: A new non-Markovian stochastic Schrödinger equation at finite temperatures is presented to correctly describe charge carrier dynamics in organic molecular crystals. The electron-phonon interactions in both site energies and electronic couplings are incorporated by the time-dependent complex-valued random fluctuations which are generated from corresponding spectral density functions. The approach is thus easily extended to investigate coherent-to-hopping charge transfer in systems with thousands of molecular si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 63 publications
1
82
0
Order By: Relevance
“…Numerical simulations have demonstrated that the approach indeed correctly predicts the carrier dynamics for symmetric systems, but it gives out incorrect long time dynamics for asymmetric systems. [27] To investigate the carrier transport in asymmetric systems, we consider molecular vibrational motions quantum mechanically, and propose a mTDWPD method satisfying the detailed balance principle. To do it, we write the phonon Hamiltonian Eq.…”
Section: The Mtdpwd Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical simulations have demonstrated that the approach indeed correctly predicts the carrier dynamics for symmetric systems, but it gives out incorrect long time dynamics for asymmetric systems. [27] To investigate the carrier transport in asymmetric systems, we consider molecular vibrational motions quantum mechanically, and propose a mTDWPD method satisfying the detailed balance principle. To do it, we write the phonon Hamiltonian Eq.…”
Section: The Mtdpwd Methodsmentioning
confidence: 99%
“…Recently, we have proposed a time-dependent wavepacket diffusion (TDWPD) method to describe the carrier dynamics [26][27][28][29] in organic semiconductors, which essentially incorporates the coherence and tunneling effects, and can be applied to large systems. In this article, we overview the TDWPD method and its applications.…”
Section: Introductionmentioning
confidence: 99%
“…This may be ascribed to vibrational progressions [48]. However, it lies outside the scope of this letter to incorporate the vibrational degrees of freedom into the absorption spectra.To investigate the quantum dynamics of the Frenkel-CT excitons in the DNTT, we apply the stochastic Schrödinger equation formulated by Zhao and coworkers [62][63][64][65]. In this formalism, time evolution of an excitonic wave function coupled to a phonon bath is obtained as follows:…”
mentioning
confidence: 99%
“…To investigate the quantum dynamics of the Frenkel-CT excitons in the DNTT, we apply the stochastic Schrödinger equation formulated by Zhao and coworkers [62][63][64][65]. In this formalism, time evolution of an excitonic wave function coupled to a phonon bath is obtained as follows:…”
mentioning
confidence: 99%
See 1 more Smart Citation